Transient left bundle branch block and poor atrioventricular conduction during ablation of accessory pathway at the left ventricle - Kuo‐Feng Chiang; Chi‐Yen Wang; Jin‐Long Huang; Yu‐Cheng Hsieh (Journal of Arrhythmia, 2020)
Abstract A 56‐year‐old female with manifest Wolff‐Parkinson‐White (WPW) syndrome was sent to emergency room because of preexcited atrial fibrillation (AF) and became sinus rhythm after cardioversion. Then, she received catheter ablation of a left‐sided lateral accessory pathway. The patient immediately developed Wenckebach atrioventricular (AV) block and left bundle branch block (LBBB) during the initial ablation. The ECG still showed LBBB 1 hour after ablation. The LBBB became narrow QRS (The QRS complex in the electrocardiogram. The QRS complex includes the Q wave, R wave, and S wave) 1 day later. Two weeks later, Holter's ECG showed normal sinus rhythm with 1:1 AV conduction even at the maximum heart rate of 125 beats/min. Transient LBBB and poor AV nodal conduction could occur during ablation by the trans‐aortic approach.